How Does Promotion Intensity Moderate the Relationship Between Growth Opportunity and Financial Constraints on Tax Aggressiveness? - Lioni Indrayani; Luh Nadi; I Ketut Wenten (CV. Ulil Albab Corp, 2026)
This study aims to examine the role of promotional intensity in moderating the relationship between growth opportunity and financial constraint on tax aggressiveness. Taxes are the primary source of state revenue, while for companies they are considered expenses that reduce net income. Consequently, companies often engage in tax planning strategies to minimize tax burdens. This research employs a quantitative approach using secondary data obtained from consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2019–2024 period. The analytical method used is Moderated Regression Analysis (MRA) supported by descriptive statistical tests, classical assumption tests, and panel data regression analysis. The results indicate that growth opportunity and financial constraint significantly affect tax aggressiveness. However, promotional intensity is unable to moderate the relationship between growth opportunity and tax aggressiveness, nor the relationship between financial constraint and tax aggressiveness. These findings suggest that promotional expenditures are not a determining factor in strengthening or weakening managerial decisions related to tax aggressiveness.